Incidencia de la flexibilidad y de la velocidad en el rendimiento técnico de la gimnasia artística en la categorís infantil de la Federación Deportiva de Chimborazo - Guamán Gavín, Galo Fabián (2010)
The work deals with the incidence of flexibility and speed in the technical performance artistic gymnastics in the category of child Chimborazo Sports Federation in the period 2009 - 2010, was chosen by the importance that did not necessary to use physical tests to assess power flexibility and speed and improve performance technical artistic gymnastics, after application of physical test we have a database of results concrete. My work has investigated all important parameters that includes a thesis such as: Preliminary pages, introduction, problematization, objectives on which we wish to achieve focus at the end of the research has also justification is the reason why was made subject. It has a theoretical framework that includes scientific content on the subject that is going to be help ascertain the impact of flexibility and speed on the technical performance of gymnastics Art.